Implementasi Algoritma C4.5 Prediksi Produksi Komoditas Tanaman Perkebunan Berdasarkan Luas Lahan - Damayanti, Desi (TIN: Terapan Informatika Nusantara, 2022)
The Blue-blue Plant Protection Development Unit (UPPT) is an agency that plays a role in assisting the community in increasing the production of plantation crop commodities in their fostered areas, both in terms of quality and quantity. However, sometimes there are still problems experienced by farmers, namely the incompatibility of the production of plantation crop commodities with the area of ​​land they have, so that it can affect the level of income of the farmers themselves. One way to process this data is to apply data mining techniques, where data mining is a process of analyzing large data that is extracted into information to determine the pattern of analysis on plantation crop commodity production data based on land area. The C.45 algorithm will later explore existing data and will form a decision tree, where the decision tree will later assist the Blue-blue Plant Protection Development Unit (UPPT) in taking good actions in helping to increase the production of plantation crop commodities. and provide counseling to fostered farmers to anticipate losses to farmers